2021
DOI: 10.1021/acscatal.0c05081
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization by C(sp3)–H Arylation with a Transient Directing Group for the Diastereoselective Preparation of Indanes

Abstract: We report Pd(II)-catalyzed cyclative C(sp 3 )−H arylation of ketones with a transient directing group (TDG). Based on calculations, the oxidative addition step implicates a highly strained trigonal bipyramidal geometry around a Pd(IV) intermediate afforded by the bidentate TDG and the intramolecular arylation process. As a consequence, unproductive protodeiodination outcompetes the cyclative arylation Pd(II/IV) pathway under standard conditions. The desired selectivity was achieved by prudent selection of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 72 publications
3
25
1
Order By: Relevance
“…This proposed mechanism is based on the presumption that Ag 3 PO 4 is first slowly converted to AgTFA before it operates as an iodide abstractor. 19 TS1-A is favored over TS1-B by 2.4 kcal/mol as a result of two contributing factors (Figure 2B). First, an attractive π−π interaction between the substrate arene and the pyridone ligand during CMD stabilizes the preferred TS1-A.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…This proposed mechanism is based on the presumption that Ag 3 PO 4 is first slowly converted to AgTFA before it operates as an iodide abstractor. 19 TS1-A is favored over TS1-B by 2.4 kcal/mol as a result of two contributing factors (Figure 2B). First, an attractive π−π interaction between the substrate arene and the pyridone ligand during CMD stabilizes the preferred TS1-A.…”
supporting
confidence: 86%
“…While previous reports have demonstrated that CMD under similar conditions is reversible, 19,69 calculations and an isotopic labeling study are consistent with accounts of mechanistic variations caused by small changes in the substrate. 70 In this case, the methylene selectivity may be due to two factors: (1) ligand−substrate interactions that promote methylene selectivity and (2) the geometry of Pd at the competing OA transition states.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Eventually, the groups of Sorensen and Yu recently disclosed a palladium-catalyzed intramolecular version of a similar process, using glycine as the transient directing mediator and pyridinone ligands, enabling the intramolecular β-arylation of ketones bearing a remote iodoarene to indanes in high to excellent yields and high diastereoselectivity, accounted for a specific well-ordered and rigid Pd(II/IV) transition state (Scheme 66, g). [120] As for the mechanism of the C(sp 3 )À H (hetero)arylation of aliphatic aldehydes or ketones, the aforementioned processes using a transient imine directing group are believed to share the one depicted in Scheme 61, starting with aliphatic aldehydes and ketones instead of aromatic ones.…”
Section: Unactivated C(sp 3 )à H Bondmentioning
confidence: 99%